2016
DOI: 10.1111/resp.12823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous positive airway pressure on diaphragmatic kinetics and breathing pattern in healthy individuals

Abstract: Background and objective: In this study, we investigate the changes in diaphragmatic kinetics, breathing pattern and work of breathing induced by 10 cmH 2 O of continuous positive airway pressure (CPAP). Methods: We used sonography to study diaphragmatic kinetics and measured energy expenditure using indirect calorimetry in 50 healthy volunteers at 0 cmH 2 O positive end expiratory pressure (ZEEP) and after application of 10 cmH 2 O CPAP. In a subgroup of 14 subjects, the changes in thoracic and abdominal volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…In healthy individuals, CPAP induces hyperinflation, which affects the length of diaphragm fibers and muscle kinetics. [23][24][25] In keeping with the results of a previous study, 23 we observed increments of 25% and 45% for thickness at end-expiration and thickness at end-inspiration, respectively, after application of CPAP 10 cm H 2 O. Further increments of both thickness at end-expiration and thickness at end-inspiration compared with CPAP were observed with CPAP ϩ HFNC 40 L/min and 50 L/min, although not 30 L/min.…”
Section: ͻ001supporting
confidence: 90%
See 2 more Smart Citations
“…In healthy individuals, CPAP induces hyperinflation, which affects the length of diaphragm fibers and muscle kinetics. [23][24][25] In keeping with the results of a previous study, 23 we observed increments of 25% and 45% for thickness at end-expiration and thickness at end-inspiration, respectively, after application of CPAP 10 cm H 2 O. Further increments of both thickness at end-expiration and thickness at end-inspiration compared with CPAP were observed with CPAP ϩ HFNC 40 L/min and 50 L/min, although not 30 L/min.…”
Section: ͻ001supporting
confidence: 90%
“…In healthy volunteers unaware of the study purposes, we found that adding HFNC to CPAP (compared to CPAP) (1) did not importantly alter either the preset airway pres- 14 (12)(13)(14)(15)(16)(17)(18)(19) 19 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 21 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) .01 †; .001* ‡; .001* § 21 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 21 (18)(19)(20)(21)…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, our use of CPAP to improve airflow obstruction was interventional in nature and thus a causal influence of CPAP via relief of airflow obstruction on respiratory parameters may be inferred. It is possible that CPAP has influences on metabolic rate other than via the upper airway: For example, in controls during wakefulness, CPAP can activate accessory respiratory muscles and may increase work of breathing 62 ; while we did not seek to quantify expiratory work of breathing, our finding that respiratory effort is reduced suggests that a CPAP-induced increase in work of breathing during sleep in patients with sleep apnea is extremely unlikely. The finding of increased VO 2 on CPAP relies on the observed increase in ventilation with CPAP in conjunction with the relative constancy of PO 2 levels.…”
Section: Limitationsmentioning
confidence: 95%
“…In healthy subjects, acute hyperinflation achieved through the application of CPAP does not decrease but, instead, increases diaphragmatic excursions. 4 Diaphragmatic excursions in clinically stable hyperinflated patients with COPD and in healthy subjects are similar. 5,6 If not hyperinflation, what else could have reduced diaphragmatic excursions?…”
mentioning
confidence: 95%